Aplicación móvil bilingüe para desarrollar habilidades gastronómicas en la población de la comunidad nativa Murui bue "Centro Arenal 2020" - López García, Luis Edgardo (2021)
This thesis presents the results of the use of a bilingual mobile application, called "Amazon Nutrition", generated with the purpose of supporting the development of gastronomic skills in the population of the native community Huitoto Murui Bue "Centro Arenal". The study population was the mothers of the community. The results show the effectiveness of the mobile application for learning about Nutrition (recipes for dishes, drinks and desserts; diseases), considering that up to 90% of the mothers know at least 3 recipes, and up to 80% already know at least a minimum of regular Nutrition content, compared to 60% who know without having used the application; in addition, a high percentage of acceptance of the recommendation and use of the application by the mothers has been observed. Finally, it is concluded that the bilingual mobile application supports the learning of Nutrition content, which serves as accessible and contextualized information in their indigenous language Huitoto Murui Bue, and can be used as an alternative to train the indigenous population of "Centro Arenal" to enhance the supply of local cuisine and help generate economic income from tourism services in the area.